Germany’s Leadership Role in the European Union: An Analysis Through Theoretical Perspectives and Contemporary Political and Economic Challenges - Abuzar Khpalwak Zazai; Aminullah Mohammadi; Ismail Roshangar (PT. Radja Intercontinental Publishing, 2025)
This research paper examines Germany’s leadership role within the European Union, drawing on European Leadership Theory alongside complementary perspectives from Neoliberalism and Neorealism. As the EU’s largest economy and a founding member, Germany occupies a pivotal position requiring the balancing of national priorities with broader European integration goals. The study aims to analyze how Germany’s leadership shapes and responds to the evolving political and economic challenges facing the Union. Employing a systematic literature review, the research analyzes secondary data collected from reputable academic databases such as JSTOR, Scopus, Web of Science, and official EU documentation portals, covering publications from 1990 to 2024. Using qualitative content analysis, the study explores Germany’s role through three theoretical lenses: the promotion of institutional cooperation and economic interdependence (Neoliberalism); power dynamics and strategic positioning within a competitive international system (Neorealism); and culturally sensitive, participative leadership that reflects European values of inclusivity and cohesion (European Leadership Theory). The findings reveal Germany’s leadership as multidimensional and adaptive, effectively combining soft and hard power to navigate contemporary challenges such as the Eurozone crisis, rising populism, Euroscepticism, and energy security issues intensified by the Ukraine conflict. Germany’s strategic engagement with EU mechanisms, including the European Stability Mechanism, underscores its commitment to stability and integration. In conclusion, the paper argues that Germany’s ability to integrate these theoretical frameworks into a cohesive leadership model is vital for sustaining EU unity, promoting deeper integration, and securing the long-term resilience of the European project.